Smart metering analytics : non-intrusive load disaggregation - Ao, Boyu (2019)
In the past, most of people concentrate on the intrusive load disaggregation. However, as the appliance of home is increasing, it is not economic to use this method. In this research, we study the non-intrusive load disaggregation.